Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.12659/msm.904682
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events Associated with Treatment of Multidrug-Resistant Tuberculosis in China: An Ambispective Cohort Study

Abstract: BackgroundAdverse events are under-appreciated negative consequences that are significant clinical problems for patients undergoing anti-MDR-TB treatment due to longer duration of treatment and more need for concurrent use of multiple second-line drugs.The aim of this study was to determine the incidence of adverse events and their impact on MDR-TB therapy and treatment outcome, and to identify possible drug-event pairs in China.Material/MethodsAn ambispective cohort study was conducted based on hospital medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
59
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 18 publications
(28 reference statements)
13
59
4
Order By: Relevance
“…Other similar studies conducted elsewhere, however, did not report gout as an adverse effect [615]. Gout is a painful rheumatic disease characterized by deposition of uric acid crystals in the joints and elevation of serum uric acid levels, leading to acute inflammatory arthritis [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Other similar studies conducted elsewhere, however, did not report gout as an adverse effect [615]. Gout is a painful rheumatic disease characterized by deposition of uric acid crystals in the joints and elevation of serum uric acid levels, leading to acute inflammatory arthritis [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…The adverse events reports on MDR-TB treatment has increased and known to be related to poor treatment outcome [3]. Zhang Y et al (2017) reported that the number of successful treatment of MDR-TB reach only 52%. The high level of poor outcome consisted of died patients (9.4%), discontinued treatment (13.7%) and not evaluated (5.1%) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang Y et al (2017) reported that the number of successful treatment of MDR-TB reach only 52%. The high level of poor outcome consisted of died patients (9.4%), discontinued treatment (13.7%) and not evaluated (5.1%) [4]. World Health Organization (WHO) also reports the same situation: successful treatment MDR-TB is only 54% while global treatment success rate is 83%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of adjunct therapies such as surgery (6), hospitalization, and patient support for treatment adherence (7), such as patient-centered directly observed therapy (DOT), also varies by program. The occurrence of adverse drug reactions to second-line TB drugs is common (1,8) and may be managed differently in different settings, particularly the permanent withdrawal of certain agents. All those factors result in wide variation in patient management and outcomes.…”
mentioning
confidence: 99%